Penetration of UV-A, UV-B and blue light through the leaf trichome layers of two xeromorphic plants, olive and oak, measured by optical fibre microprobes - Karabourniotis, George; Bornman, Janet F. (Physiologia Plantarum, 1999)
Quartz fibre-optic microprobes were used to monitor the light microenvironment beneath trichome layers of the xeromorphic leaves of two Mediterranean evergreen sclerophylls, Olea europaea and Quercus ilex. Young developing leaves of both plants were densely pubescent on both surfaces of the lamina, whereas the mature leaves were pubescent only on the abaxial side. Trichome layers of young as well as of mature leaves of both plants attenuated almost all incident ultraviolet (UV)-B (310 nm) and UV-A (360 nm) radiation and a considerable portion of blue light (430 nm). Abaxial trichome layers of young leaves were more effective in screening out the incident radiation compared to the adaxial ones of the same leaves and also compared to the abaxial layer of the mature leaves. The abaxial epidermis of dehaired mature leaves of O. europaea was ineffective in absorbing most of the incident UV-B and UV-A radiation. UV and visible spectra beneath trichome layers of O. europaea in mature leaves confirmed that the light microenvironment on the epidermis was deprived in the UV-B, UV-A and partly in the blue spectral regions. It is proposed that the occurrence of a dense trichome layer, especially in young leaves, may play a protective role against not only UV-B radiation damage, but also against high visible irradiance. This function is performed irrespective of the differing anatomy of individual hairs of both plants. The protection provided by the trichomes could afford advantages under stress conditions, especially during leaf development.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers
Keywords: Abaxial; Adaxial (voyant); leaves; light; trichome layers